Chapter Strategie di formazione delle parole in varietà iniziali di polacco L2 - Saturno, Jacopo (Biblioteca di Studi Slavistici, 2016)
This paper describes word formation as observed in the earliest stages of L2 Polish. 31 L1 Italian beginning learners took part in a 14-hour Polish course, which was recorded, transcribed and morphologically tagged in order to correlate learner output with the relevant input features. After 4:30 hours, the learners could produce new words using the derivational suffix -k-, which in the input can be found in the majority of feminine nouns. This finding suggests that after minimal exposure, learners can identify the morphological structure of a class of nouns and reproduce it in their output.